Trend analysis of end-of-life care between hospice and nonhospice groups of cancer patients in Taiwan for 2002–11 - Chiang, Jui-Kun (Medicine (Baltimore), 2017)
The aim of the study is to examine the effect of hospice care on quality of end-of-life (EOL) care for patients with advanced cancer in Taiwan between 2002 and 2011. It is a population-based longitudinal study following National Health Insurance medical care claims of hospice and nonhospice patients with advanced cancer in their last month of life. Utilization of hospice service doubled from 10.5% to 21.5% over the study period. Of 12,682 patients identified as having advanced cancer, 7975 (62.88%) were found to have 1 or more quality indicators (QIs) of poor EOL cancer care. After adjustments, those receiving hospice cares had a significant reduction in incidence of chemotherapy in the last 14 days of life as well as intensive care unit (ICU) admission and cardiopulmonary resuscitation (CPR) in the last month of life. The hospice care group also had significant increases in having more than 1 hospitalization and dying under hospital care, but no change in having more than 1 emergency room (ER) visit. The hospice group curve of estimated incidence rates of each QI was consistently below that of the nonhospice group in chemotherapy—with the difference between the 2 curves increasing over time—ICU admission, and CPR, and above that of the nonhospice group for dying in a hospital and having more than 1 hospitalization over the study period. The 2 groups overlapped on ER visits. Overall, hospice care was associated with less chance to have 1 or more QIs of EOL care for advanced cancer patients (RR = 0.56, 95% CI: 0.52–0.60, P < .001). The utilization of hospice services doubled over the 10-year study period. Hospice care was associated with better EOL care in patients with advanced cancer.